EFFECT OF TRIPTOLIDE ON PROLIFERATION AND APOPTOSIS OF ANGIOTENSIN II-INDUCED CARDIAC FIBROBLASTS IN VITRO: A PRELIMINARY STUDY - Liu, Mao; Yeh, James; Huang, Yin; Redondo, Alfredo; Ke, Jianting; Yao, Jierong; Tan, Guangyi; Tang, Wenyi; Chen, Jian (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The effect of triptolide (TPL) on cardiac fibroblasts (CFbs) and cardiac fibrosis remain unknown till now.This study was conducted to explore the effects of TPL on proliferation and apoptosis of angiotensin II (AngII)-induced CFbs.Materials and Methods: Ang II was used to promote proliferation of CFbs. Two dosages of TPL (10ng/ml and100ng/ml) were chosen. MTT assay was used to detect cell survival rate in vitro. Flow cytometer was performed toanalyze apoptosis of CFbs. Hydroxyproline concentration was detected with hydroxyproline assay kit. Quantitativereal-time PCR was used to detect the expression of TGF-